Intratesticular Angiolipoma: A Rare Case of Adipose Tissue Presence in the Testis - V. Kalyvas; C. Gkekas; D. Papadopoulos; A. Malioris; S. Milias; M. Papathanasiou; N. Kalinderis; K. Moysidis; K. Hatzimouratidis (Case Reports in Urology)
Introduction. Solid, fat-containing tumors of the testes are extremely rare with only a few cases having been reported so far, contrary to the more frequent occurrence of paratesticular lipomatosis. Testicular angiomyolipomas and gonadal involvement in Cowden’s disease, although infrequently occurring, are known examples of fat-bearing testicular lesions. Hereby, we present an extremely rare case of intratesticular angiolipoma. Angiolipomas are benign tumors of the subcutaneous tissue commonly occurring in the trunk and the extremities. Histologically, they are characterized by ample vascularity and an excess of mature adipocytes. Definitive diagnosis is established by biopsy of the lesion. Presentation of the Case. A 35-year-old patient presented to our andrology outpatient clinic for fertility assessment. Physical examination of external genitalia revealed no significant pathology. Testicular ultrasound however depicted an isoechoic lesion on the upper pole of the right testis measuring 1.8 cm×0.8 cm×1 cm and exhibiting intense arterial flow. After sonographic and MRI investigation, the patient was referred for semen analysis and cryopreservation. Subsequently, the patient underwent testicular biopsy (frozen section biopsy) and right partial orchiectomy. Final histology reported a noninfiltrating testicular angiolipoma. No recurrences have been observed in the follow-up period. Discussion. Angiolipomas, which mainly occur in the trunk and extremities, are classified as infiltrating and noninfiltrating. The diagnosis is based on both clinical and histologic criteria, and the main method of treatment for both types is by surgical excision. The infiltrating type exhibits higher recurrence rates. Conclusion. Angiolipomas commonly occur in the subcutaneous tissue and have been invariably treated by radical excision. Hereby, we report the first case of an intratesticular, noninfiltrating type angiolipoma which was treated by partial orchiectomy.